2011
DOI: 10.5338/kjea.2011.30.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Factors and Heavy Metals on the Growth and Phosphorus Removal of Alcaligenes sp.

Abstract: BACKGROUND:This study was performed to evaluate the effects of environmental factors and heavy metals on the growth and phosphorus removal capacity of Alcaligenes sp., which was well known as one of PAOs(Phosphorus Accumulating Microorganisms). METHODS AND RESULTS: The environmental factors used in this study were temperature, pH and carbon sources, and the heavy metals included Cu, Cd, Zn, As, and Ni. The growth and P removal efficiency of Alcaligenes sp. was maximal as temperature, pH, and carbon source were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…It was reported in the previous studies that these bacteria can be used in the biological P treatment and showed the high P removal efficiencies under the best optimal conditions (Kim et al, 2010;Yoo et al, 2011;Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in the previous studies that these bacteria can be used in the biological P treatment and showed the high P removal efficiencies under the best optimal conditions (Kim et al, 2010;Yoo et al, 2011;Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%